Teaching and learning in the third space to engender shared Malaysian identity - Idrus, Faizah (2012)
Cultural tension in Malaysia have escalated in the past 5 years bringing a whole host of undesirable impacts on the nation’s economy and, most importantly, on inter-ethnic relationships. Thus, this study proposes the need to construct a shared Malaysian identity, starting from the classroom, which is facilitated by teachers through the use of short stories written by Malaysians. This proposition, amidst the differences in cultural, religious and beliefs systems, aims to close the ethnic and cultural divide and cultivate widespread inter and intra cultural awareness. The study is grounded in the notion of hybridity in the Third Space espoused by Bhabha (1994) and ameliorated and geared towards the classroom context by the works of Gutierrez (1999, 2004, 2008). The inquiry was designed using primarily qualitative research instruments employing non-participant classroom observations, semi-structured interviews with 7 English Language teachers, and group interviews with 6 groups of students from 4 different schools in Kuala Lumpur. This data source was then supported by secondary quantitative data derived from self-completion questionnaires administered to the students of the teachers involved in this study. Data analysis was guided by the main research question: To what extent can the notion of the Third Space be helpful in the construction of shared Malaysian identity? The findings from the analyses of the results show various attitudes, beliefs and teaching and practices in the English language classroom in response to the notion of constructing a shared identity in the Third Space.